Charge dynamics in alkanedithiols-additives in P3HT : PCBM bulk heterojunction solar cells - Solanki, Ankur (2015)
Addition of a small fraction of high boiling point solvent into the host of donor/acceptor blend is one the best approach to control the morphology in order to enhance the power conversion efficiency of organic bulk heterojunction (BHJ) solar cell devices. Herein, we focus on the effect of two thiol-based additives (1,6-hexanedithiol (HDT) and 1,5-pentanedithiol (PDT)) on the charge dynamics of P3HT:PCBM blend system, studied by transient absorption spectroscopy (TAS) and correlated with the solar cell device performance. TAS reveals a more efficient charge generation and polaron formation in the systems with additives as compared to those without (NA systems), at the onset which persists up to few microseconds. The recombination dynamics also exhibits the reduced recombination losses on adding these additives in this system; however, there is marginal change of recombination dynamics in PDT added system with the control. These charge dynamics were validated using the analytical model proposed in our previous work and also correlated with improved device performance (ηNA = 0.9%, ηHDT = 2.7%, ηPDT = 1.6%).